A robust multi-image phase retrieval. (February 2018) - Guo, Cheng; Shen, Cheng; Tan, Jiubin; Bao, Xuejing; Liu, Shutian; Liu, Zhengjun
Highlight: A new robust hybrid algorithm of phase retrieval is proposed. The high accurate result can be obtained with this method. The convergence performance of iterative scheme is improved. Abstract: The phase evaluation is not perfect by using three kinds of existing multi-image phase retrieval methods. The amplitude-phase retrieval scheme is employed for initializing the input of the Multi-stage algorithm to obtain a robust result. The synthesized axial multi-image phase retrieval technique is able to be highly accurate convergent with continuous phase distribution of [0, 2π] and random phase distribution of [0, π], which is also demonstrated to have sharper edge for reconstructed phase map in experiment. This paper will provide a powerful and useful guidance for axial multi-image phase retrieval.